Pengembangan dan Pelayanan Kepala Sekolah dalam Mempertahankan Nilai Prestasi Akademik - Husni, Muhammad (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
In the effort of human empowerment, education plays an important role. Improving the quality of human a process related to of improving the quality of education. National education is faced with of the low quality of education, especially the level of primary and secondary education. Improving the quality of education continues to be carried out by various parties as an awareness of the importance of character education. The goal is to determine the performance of the Principal as a leader and provide services in improving achievement. The results of the study were that principals had provided services and supervision, and empowered their education personnel, supervised periodically and established cooperation and gave an example.